Effect of sodium hypochlorite under several formulations on root canal dentin microhardness - Garcia, Arturo J.A.; Kuga, Milton C.; Palma-Dibb, Regina G.; Só, Marcus V.R.; Matsumoto, Mariza A.; Faria, Gisele [UNESP]; Keine, Kátia C. (Wiley, 2013)
Aim The aim of the present study was to evaluate the effect of three different formulations of sodium hypochlorite on the microhardness of root canal dentin in cervical and apical segments. Methods Twenty-four extracted human teeth had their roots sectioned along their long axes in a buccolingual direction. One half of each root was selected, and transversely sectioned resulting in two segments, cervical and apical, with similar lengths. The specimens were divided into three groups (n = 16), according to the sodium hypochlorite formulation used: (a) group 1, 2.5% sodium hypochlorite; (b) group 2, Chlor-XTRA; and (c) group 3, 5.5% sodium hypochlorite gel. These groups were subdivided in two subgroups (n = 8): cervical and apical root segments. Before testing the substances, dentin microhardness was measured on each section, 100 μm from the root canal with a Knoop tester. After 15 min of application, a new measurement was performed on each segment. Data were collected and registered for statistical treatment. Results In both segments, the substances reduced dentin microhardness. No differences were observed between the groups, independent of the analyzed segment (P > 0.05). Conclusions All substances reduced dentin microhardness. Chlor-XTRA and 5.5% sodium hypochlorite gel promoted a reduction similar to the 2.5% sodium hypochlorite solution.
Keywords: dentin; detergent; endodontic; microhardness; sodium hypochlorite